2015
DOI: 10.1177/2047487315607041
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of intensive follow-up on the long-term prognosis of percutaneous coronary intervention in acute coronary syndrome patients – a single center prospective randomized controlled study in a Chinese population

Abstract: A cardiologist-coordinated intensive follow-up program markedly decreased cardiovascular risk factors, reduced medical costs, promoted medication adherence and improved the long-term prognosis of patients after percutaneous coronary intervention in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…This finding highlights the importance of multi-professional collaboration to predict patient adherence, which was also reported by Valaker et al (2017) In the acute phase, after PCI, the therapeutic relationship between patients and their cardiologist is an important predictor for adherence to treatment, 7 and the resources for this should be guaranteed despite the scarce number of cardiologists. This result is in line with Du et al (2016), who confirmed that counselling coordinated by a cardiologist is effective for decreasing cardiovascular risk factors and promoting adherence to treatment. In the present study, support from nurses was associated with lower total cholesterol in line with the finding reported in numerous of studies that confirmed that nursing interventions had a positive impact on improving patients' health behaviour and managing risk factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding highlights the importance of multi-professional collaboration to predict patient adherence, which was also reported by Valaker et al (2017) In the acute phase, after PCI, the therapeutic relationship between patients and their cardiologist is an important predictor for adherence to treatment, 7 and the resources for this should be guaranteed despite the scarce number of cardiologists. This result is in line with Du et al (2016), who confirmed that counselling coordinated by a cardiologist is effective for decreasing cardiovascular risk factors and promoting adherence to treatment. In the present study, support from nurses was associated with lower total cholesterol in line with the finding reported in numerous of studies that confirmed that nursing interventions had a positive impact on improving patients' health behaviour and managing risk factors.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the accumulation of risk factors and the increasing prevalence of hypertension, obesity and diabetes are more common among women compared to men. 29 It is interesting to note that, in the 2013 baseline study, support from nurses was not a statistically significant predictor of adherence to treatment, but support from physicians was a significant predictor of females' motivation to adhere to treatment. 7 However, six years after PCI, both support from nurses and support from physicians were significant predictors of adherence.…”
Section: Discussionmentioning
confidence: 95%
“…Participants in the intervention group received medical consultations from a cardiologist through phone calls at 3, 6, 12 and 36 months postdischarge. The study found that the intervention group had significantly better medication adherence 38. Similarly, Li et al 39 used phone call interviews to educate participants with myocardial infarction on relevant knowledge after discharge and found this intervention was effective in improving medication adherence.…”
Section: Resultsmentioning
confidence: 95%
“…Du et al 38 randomised 964 patients with CHD into an intervention or control group. Participants in the intervention group received medical consultations from a cardiologist through phone calls at 3, 6, 12 and 36 months postdischarge.…”
Section: Resultsmentioning
confidence: 99%
“…However, based on the results of this study, during the acute phase after PCI, physician support is predictor of adherence to treatment. The therapeutic relationship between patients and physicians is important and the resources needed for this relationship should be guaranteed, as Du et al () have confirmed: cardiologist‐coordinated intensive follow‐up programmes have decreased cardiovascular risk factors, reduced medical costs, promoted adherence to medication and improved the long‐term prognoses of patients after PCI.…”
Section: Discussionmentioning
confidence: 99%